Detection of multi-nutrients deficiency in cereal plants by the use of chlorophyll fluorescence - Zuzanna Malwina Jaszczuk; Wojciech Bąba (Journal of Water and Land Development, 2024)
Nutrient deficiency (ND) stands as a prominent environmental factor that significantly impacts global plant growth and productivity. While numerous methods have been employed for detecting nutrient deficiencies in plants, many of them are invasive, time-consuming, and costly. In contrast, chlorophyll fluorescence (ChlF) signals have emerged as a non-destructive tool for the identification of specific nutrient deficiencies, such as nitrogen (N), phosphorus (P), and potassium (K), across various plant species. In this pioneering study, ChlF measurements were employed for the first time to detect a combination of nutrient deficiencies, including deficiencies in nitrogen and phosphorus (–NP), nitrogen and potassium (–NK), potassium and phosphorus (–KP), and a complete NPK deficiency (–NPK). The experiment was conducted using wheat (Triticum aestivum) and maize ( Zea mays) plants, which were grown under controlled laboratory conditions. An optimal hydroponic system was established to facilitate eight experimental conditions, namely: control, –N, –P, –K, –NP, –NK, –KP, and –NPK. Measurements were systematically collected at two-day intervals over a span of 24 days. Our findings demonstrate that chlorophyll fluorescence signals can enable the differentiation of various nutrient deficiencies even prior to the onset of observable symptoms. Furthermore, the examination of chlorophyll fluorescence parameters enables us not only to identify a singular macronutrient deficiency but also to detect multiple macronutrient deficiencies concurrently in a plant.